(untitled) (International Journal of Physiotherapy, 2019)
Background: Nonspecific low backache is a pain, muscle tension, or stiffness localized between the costal margin and inferior gluteal folds, without sciatica. Only 10% of the cases have a specific cause. One of the risk factors is poor hamstring flexibility. Mulligan’s BLR and IASTM have shown to improve hamstring flexibility. No studies have compared both. Therefore the study was undertaken. Methods: 48 subjects, mean age 34.27 ± 5.30 were recruited. Group A (24 - 15 male and 9 female) received TENS, Mulligan’s BLR and conventional exercises. Group B (24 - 12 male and 12 female) received TENS, M2T for Hamstrings and conventional exercises. Outcome measures were taken pre-treatment session 1 and post-treatment session 6. Results: Pre and post mean the difference in group A [BLR] was 5.96 ± 0.95 for NPRS, 19.38 ±7.28 for Right AKET, 20.54 ± 6.78 for Left AKET, 2.07 ± 6.49 for Lumbar lordosis and 28.38 ± 9.73 for QBPDS. Pre and post mean the difference in group B [M2T] was 5.71 ± 1.20 for NPRS, 17.00 ± 6.94 for Right AKET, 15.75 ± 6.50 for Left AKET, 1.20 ± 4.76 for Lumbar lordosis and 26.42 ± 11.38 for QBPDS. The intragroup comparison was statistically significant, p = 0.0001 for all outcome measures. Intergroup comparison was statistically significant, p < 0.05 for Left AKET (p=0.0161). Conclusion: Interventions given were equally effective in reducing pain, improving hamstring flexibility, and reducing disability within the group but not between the groups except left AKET.